Exploring the Mediating Role of Growth Mindset in the Relationship Between Attachment Styles and Mental Health Among College Freshmen - Tao W; Zheng L; Wang W; Tao X (Psychology Research and Behavior Management)
Weidong Tao,1 Lan Zheng,1 Wenbo Wang,1 Xiaoli Tao2 1Department of Psychology, School of Education (School of Teacher Education), Huzhou University, Huzhou, Zhejiang, 313000, People’s Republic of China; 2Department of Preschool, School of Education (School of Teacher Education), Huzhou University, Huzhou, Zhejiang, 313000, People’s Republic of ChinaCorrespondence: Weidong Tao, Department of Psychology, School of Education (School of Teacher Education), Huzhou University, No. 759, East 2nd Road, Huzhou, Zhejiang, 313000, People’s Republic of China, Tel +86 13515723180, Email 02555@zjhu.edu.cnPurpose: College freshmen face a heightened risk of mental health problems. Recent research has extensively explored attachment and growth mindset as key factors that influence mental health. However, the specific relationship between attachment and growth mindset remains unclear. This study aimed to investigate how attachment impacts the growth mindset of college students and explore the relationship between growth mindset, attachment, and mental health.Methods: A survey of 684 college freshmen (80.1% female, average age 18.4) at a university in Huzhou was conducted using the Growth Mindset Scale, Adult Attachment Scale, and Symptom Checklist (SCL-90) and a demographic questionnaire to collect basic information about participants.Results: The findings show that attachment security positively predicted growth mindset (β=0.16), whereas attachment insecurity negatively predicted growth mindset (β=− 0.22). The research highlights that a growth mindset mediates the association between attachment security and mental health, and between attachment insecurity and mental health.Conclusion: The results highlight the importance of fostering a secure attachment style and promoting a growth mindset as key factors for improving mental health. These findings suggest that incorporating growth mindset strategies into mental health education and interventions could help students with diverse attachment styles enhance resilience and better manage psychological challenges.Keywords: mental health, SCL-90, attachment, growth mindset, college freshmen